2019
DOI: 10.1038/s41388-019-1023-z
|View full text |Cite|
|
Sign up to set email alerts
|

Active PLK1-driven metastasis is amplified by TGF-β signaling that forms a positive feedback loop in non-small cell lung cancer

Abstract: Early findings that PLK1 is highly expressed in cancer have driven an exploration of its functions in metastasis. However, whether PLK1 induces metastasis in vivo and its underlying mechanisms in NSCLC have not yet been determined. Here, we show that the expression of active PLK1 phosphorylated at T210, abundant in TGF-β-treated lung cells, potently induced metastasis in a tail-vein injection model. Active PLK1 with intact polo-box and ATP-binding domains accelerated cell motility and invasiveness by triggerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 41 publications
6
73
0
Order By: Relevance
“…S4 shows a positive correlation between the expression of ALKBH4 and E2F1 , as well as between that of ALKBH4 and E2F1-target genes, which were only observed in early stage NSCLC tumour tissues, but not in those of late stage NSCLC. Among the Polo-like kinase (PLK) family, PLK1 and PLK4 are highly expressed in NSCLC 47 , 48 and promote metastasis via epithelial–mesenchymal transition (EMT) induction 49 , 50 . Since ALKBH4 knockdown downregulated the expression of PLK1 and PLK4 (Supplementary Table S2 ), ALKBH4 may function as a tumour promoter by accelerating cancer cell proliferation via upregulation of E2F1 signalling in early stage, and by promoting metastasis via upregulation of PLK signalling in late-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…S4 shows a positive correlation between the expression of ALKBH4 and E2F1 , as well as between that of ALKBH4 and E2F1-target genes, which were only observed in early stage NSCLC tumour tissues, but not in those of late stage NSCLC. Among the Polo-like kinase (PLK) family, PLK1 and PLK4 are highly expressed in NSCLC 47 , 48 and promote metastasis via epithelial–mesenchymal transition (EMT) induction 49 , 50 . Since ALKBH4 knockdown downregulated the expression of PLK1 and PLK4 (Supplementary Table S2 ), ALKBH4 may function as a tumour promoter by accelerating cancer cell proliferation via upregulation of E2F1 signalling in early stage, and by promoting metastasis via upregulation of PLK signalling in late-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, attention should be paid to some pathways including R-HAS-2500257: resolution of sister chromatid cohesion; GO: 0051301: cell division; CORUM: 1118: chromosomal passenger complex (CPC, including CDCA8, INCENP, AURKB, and BIRC5); CORUM: 127: NDC80 kinetochore complex; M129: PID PLK1 pathway; and GO: 0007080: mitotic metaphase plate congression. Previous studies show that the Polo-like kinase 1(PLK1) is highly expressed in LC, which predicts the poor survival in metastatic LC patients [56,57]. In addition, the PLK1 pathway plays a certain role in the progression of HCC [58], glioma [59], and lung adenocarcinoma [60].…”
Section: Discussionmentioning
confidence: 99%
“…They also found that both cell cycle-related gene sets (G2/M check point and E2F targets) and MYC target gene sets were enriched insamples with high PLK1 expression via Gene Set Enrichment Analysis. It also has been reported that PLK1 up-regulated TGF-β signaling to drive cancer cell invasiveness in vitro and served as a strong predictor for diminished survival rates in metastatic NSCLC patients [35]. Many previous studies have suggested that downregulating PLK1 expression could strongly repress cell growth and lead to apoptosis in many types of tumors, indicating that PLK1 could be a promising treatment target for cancers [36][37][38].…”
Section: Discussionmentioning
confidence: 99%